Public Resource Spending and its Impact on Territorial Development: the Brumadinho Case (Research, Society and Development, 2020)
This article aims to analyze to what extent the form of budget resource expenditure impacts territorial development in a mineral-based municipality. The case chosen was the municipality of Brumadinho-MG. Data collection occurred through documentary and bibliographic research. This is a qualitative and exploratory research using the technique of content analysis to interpret the data. The main conclusions: the municipality does not take advantage of the potential short-term mining resource flow (royalties) to invest in development projects that diversify local productive structures, so it does not prioritize budget spending on economic activities with the highest potential for productive inclusion. population such as Cultural Tourism and Agriculture. In addition, it uses little resource in Environmental Management. Finally, the disaster that struck disrupted their municipal finances and impacted other alternative mining activities.